Appraising Agriculture Development Strategy of Nepal from Agricultural Extension Perspective - Pasa, Rajan Binayek; Joshi, Hem Raj; Acharya, Mahendra; Adhikari, Jeevan (Journey for Sustainable Development and Peace Journal, 2024)
Nepalese economy is primarily dependent on agriculture which provides employment to the vast majority (>60.02%) of the people. The goal of the Agriculture Development Strategy (ADS) is to make agriculture sector more productive, equitable, and sustainable driver for upgrading Nepalese economy. This library based paper thus aims to appraise ADS from extension perspective which is essential for educating farmers about new ideas and information related to agriculture development. The study thoroughly appraises ADS programs, policy documents, scholarly articles and secondary data fact supplemented to the research issue educating and supporting farmers. The result of the appraisal show that implementation of a voucher system and the decentralized strategy of establishing Service Centers for Community Agriculture Extension in each Village Development Committee, use of ICT and GESI based approaches are praiseworthy. However, there are still major obstacles to overcome resource constraints, implementation hurdles, and unclear roles due to the federal governance transition. The paper concludes that to enhance betterment of the ADS, there is a need for increased funding, capacity building, and improved infrastructure. Additionally, stronger monitoring and evaluation systems, along with promoting public-private partnerships and ensuring active farmer participation are essential. Addressing these issues is crucial for achieving goals and objectives of the ADS.